A Comparative Study of Multiple Sequence Alignments - Karmakar, R; Sadhu, TK; Hazra, A; Sahana, S; Karmakar, S (International Journal of Computer Sciences and Engineering, 2025)
Multiple sequence alignment is a very useful tool[18]. It is used to solve different Biological sequence alignment problem like DNA and Protein sequences[3]. There are many ways to solve multiple sequence alignment problems. Dynamic programming method is used to produce MSA directly[23]. Nowadays, progressive alignment approach and iterative approach are the important methods to solve MSA problems. This paper discussion is about some progressive alignment and iterative Multiple Sequence Alignment algorithm methods and compare their performances.